(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article provides a comprehensive legal and theoretical analysis of the subjective elements of crimes involving the illegal handling of potent or toxic substances. The subjective side of a crime is considered one of its fundamental components, encompassing the identity of the perpetrator and their internal psychological state. Although the Criminal Code of the Republic of Uzbekistan does not provide a precise definition of the subject of a crime, this issue is addressed through the concepts of a “person who committed a crime” or an “offender” in existing legal documents. The article emphasizes that a person must be a physical individual who has reached the legal age of criminal responsibility and possesses mental capacity in order to be considered the subject of a crime. The essential requirements for criminal liability are explained in detail, including physical personhood, legal age, and mental soundness. Additionally, the concept of mental capacity is explored from both medical and legal perspectives, highlighting the conditions under which it applies and how a person’s state – particularly under the influence of narcotic or psychotropic substances – affects criminal behavior. The article analyzes how crimes committed under the influence of such substances may impair an individual’s willpower and limit their understanding of the social danger of their actions. From a legal standpoint, it is noted that if a person knowingly places themselves in a state of mental incapacity, they should still bear criminal responsibility. This concept is examined through the lens of the legal doctrine of astio libera in causa. The findings presented in the article serve as an important resource for the proper qualification of crimes and the fair imposition of penalties in cases involving potent and toxic substances. The article stresses the importance of studying this issue not only from a legal perspective but also from social and medical angles.